Analisa Penjualan Produk Oli Dengan Metode Data Mining Asosiasi Algoritma Apriori Pada PT. Mitra Petra Sejahtera - Putri Septiani Azura; M. Safii; Fitri Rizki (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2021)
Competition in the business world makes business people have to think harder in developing strategies to deal with such competition. Marketing strategy requires a reference so that promotion is right on target, for example by looking for similarities between product items. This research was conducted by applying the association rule a priori algorithm method to the sales transaction dataset, to form a candidate combination between product items. The sales transaction dataset was taken in January to December 2019. In this study, a minimum support value of 25% and a minimum confidence value of 60% were determined with data processing using Microsoft Excel and RapidMiner software. A priori algorithm can produce association rules as a reference in product promotion and decision support in providing product recommendations to consumers based on the specified minimum support and confidence values.